AMINA OXÃDASE EM PLANTAS. II. ATIVIDADE DURANTE A GERMINAÃ‡ÃƒO DE ð˜—ð˜©ð˜¢ð˜´ð˜¦ð˜°ð˜ð˜¶ð˜´ ð˜·ð˜¶ð˜ð˜¨ð˜¢ð˜³ð˜ªð˜´ - Gutierrez, Luiz E.; Basso, Luiz C.; Brancalion, Maria J. (REVISTA DE AGRICULTURA, 2020)
AMINA OXÃDASE EM PLANTAS. II. ATIVIDADE DURANTE A GERMINAÃ‡ÃƒO DE ð˜—ð˜©ð˜¢ð˜´ð˜¦ð˜°ð˜ð˜¶ð˜´ ð˜·ð˜¶ð˜ð˜¨ð˜¢ð˜³ð˜ªð˜´